Ongoing research on seismic safety assessment - Raimundo Delgado (2010)
Research on seismic safety assessment has been the centre of great interest among the scientific community in recent years. Although the devastating impact of earthquakes on current society should be incentive enough to increase research, the development of more realistic mechanical behaviour models and the continuous enhancement of computation capabilities are paramount factors contributing a great deal to the increase of such interest. In this context, three research areas can be identified as currently leading to important developments: code related research, especially in Europe where new design codes are in the implementation process; risk analysis, namely concerning the definition of methodologies for safety assessment that involve the evaluation of the failure probability and could be included in future generations of codes; and experimental characterization of constitutive laws which provides support for the development and calibration of accurate and realistic numerical models for seismic analysis and for the adequate characterization of limit state capacities. The paper will present some of the current scientific research trends on these three seismic safety assessment related topics. Studies addressing the seismic safety assessment of structures, either probabilistically or based on code provisions, and that consider realistic nonlinear mechanical behaviour models will be focussed. Reference will also be made to experimental research on the seismic behaviour of structural elements, emphasizing its crucial role to support the development of numerical models simulating the effects of different seismic strengthening techniques. Finally, given the development of studies leading to new trends and perspectives for performance based earthquake engineering, a possible scenario for seismic design in the future is presented, emphasizing the key issues for its implementation.